Disintegrating Europe the twilight of the European construction - Hama, Noriko 1952- (Praeger, 1996)
Hama likens the situation to Wagner's cycle of operos, Der Ring, and wonders whether the European Union idea is as imperishable as the Europeans themselves maintain. When Wagner's hero Siegfried dies, the existing order dies with it in a Gotterdammerung, a "twilight of the gods" - and Hama argues that the flames that are presently destroying the Union's equivalent of Siegfried's hall may well be destined to devour eventually the whole castle of the European Valhalla itself. This approach is dramatic, readable, and compelling, and represents the first time that so qualified an economic commentator has attempted a 'big picture' view of the future of the European unification project
Keywords: Europäische Union; European Union; Wirtschaft; Economic forecasting -- Europe; Entwicklung; Wirtschaftspolitik; Europäische Integration; Europa; Europe -- Economic conditions -- 1945-